Positive Psychology applied to education in Practicing Teachers during the COVID-19 Pandemic: Personal Resources, Well-Being, and Teacher Training (2022)
Teaching has often been linked to psychosocial problems, and is an occupation in which the implementation of strategies for the improvement, updating and promotion of the mental health of those involved is essential. Accordingly, this study assessed the effectiveness of a program aimed at improving psychological well-being, optimism, self-efficacy, and self-esteem as well as at reducing psychological distress in teachers. The study was quasi-experimental and comprised 24 teachers from technical, secondary, and elementary schools in Uruguay. The constructs were measured before and after the program, which was conducted during the COVID-19 pandemic and comprised 12 modules in a multicomponent intervention format. The results indicate a significantly low magnitude increase in well-being (F = 5.36, p = 0.033, Cohen’s d = 0.47) and a moderate increase in self-efficacy (F = 9.14, p = 0.008, Cohen’s d = 0.62). Similarly, a significant decrease was observed in psychological distress of mild effect (F = 5.80, p = 0.028, Cohen’s d = 0.49). To conclude, interventions based on positive psychology improve teachers’ well-being, enhance other psychological resources, and reduce psychosocial risks such as discomfort. Thus, these interventions can be devices for career development and teacher updating.